A PENGARUH CAPITAL ADEQUACY RATIO DAN NON PERFORMING FINANCING TERHADAP RETURN ON ASSET PADA BANK SYARIAH YANG TERDAFTAR DI BURSA EFEK INDONESIA: CAPITAL ADEQUACY RATIO DAN NON PERFORMING FINANCING - Dasmi Husin Dasmi; Ihsan Arief (JAKTABANGUN: Jurnal Akuntansi dan Pembangunan, 2023)
This study aims to determine the effect of Capital Adequacy Ratio and Non-Performing Financing on Return On Assets in Islamic banking companies listed on the Indonesia Stock Exchange (IDX). The population of this study is all Islamic banking companies listed on the IDX in 2015-2018. The sampling technique used in this study was purposive sampling. The data obtained is quarterly data from published reports of Islamic banks listed on the IDX for three years, namely 2015-2018. The data analysis technique used is panel data regression analysis method. This study used the Eviews 10 statistical analysis tool. During the observation period it showed that the research data were normally distributed. The results of the F test show that the results of the Capital Adequacy Ratio and Non-Performing Financing have a significant effect on Return On Assets. The results of the t test show that the Capital Adequacy Ratio and Non-Performing Financing have a significant effect on Return On Assets